Reliability Theory Application of Bipolar Network in Monitoring and Detecting Network Intrusion - Binh, Doan Thanh; Hien, Nguyen Trung; Ha, Do Manh; Nhung, Dinh Thi (Old Journal, 2019)
Today the rapid and widespread development of computer networks and computer network environments brings many risks and threats to network security that cause loss or change data of information systems. Security attacks that change the state and components of the system will leave traces, so tracking for network security attacks is of interest. Depending on the monitoring environment and the protocols used to transmit information between network nodes, tracking of network security attacks is done in different ways. Network security attacks affect the communication of information between network nodes, changing the dynamic relationship between network nodes and their reliability. The problem of evaluating internal network reliability to trace network intrusion detection is given and resolved in this article.